Simultaneous Isolation of Chryseobacterium gleum from a Case of Blood Stream Infection and Pneumonia: A Rare Isolate - Shabnum, M.; Reddy, P. Sreenivasulu; Vasundhara, P. (Highlights on Medicine and Medical Research Vol. 15, 2021)
Chryseobacterium gleum is a gram-negative, non-fermentative, catalase and oxidase-positive pathogen that is emerging as a multidrug-resistant pathogen in health-care settings, especially in cases of bloodstream infection, urinary tract infection, and pneumonia. So far, only a few cases of Chryseobacterium species have been identified. Given the high mortality rates associated with these pathogens, fast and accurate identification methods are essential for better patient care. In this paper, we describe a case of bloodstream infection and pneumonia in a 60-year-old female patient with k/c/o CKD/ Type 2 DM/ HTN/ CAD who was admitted to the emergency room with a high-grade fever for the past 10 days and breathlessness for the past three days. Two paired blood cultures and an ET culture isolated Chryseobacterium gleum with identical susceptibility patterns for Cephalosporins, Carbapenems, and Colistin, as well as susceptibility to Levofloxacin, Cotrimoxazole, and Minocycline. On Levofloxacin treatment, the patient's clinical condition improved. It's extremely rare to extract a rare isolate called Chryseobacterium gleum from both the bloodstream and the lower respiratory tract at the same time. Because of the inherent resistance to Carbapenems and Colistin, early laboratory detection is needed to guide effective antibiotic therapy, reducing the risk of health-care-associated infections.